New Straits Times, 18 August 2008 - Noor Adzman Baharuddin; Adib Povera (The New Straits Times Press (M) Bhd, 2008)
Local universities should step up their capacity building to meet the growing demand for places of study, said Datuk Seri Abdullah Ahmad Badawi.